2014
DOI: 10.1002/cctc.201301061
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment for Conductive 12 CaO⋅7 Al2O3 Electride Powder by Rapid Thermal Annealing Processing and Its Application to Ammonia Synthesis

Abstract: The inorganic electride [Ca24Al28O64]4+(e−)4 (C12A7:e−) has unique properties, that is, chemical stability and a low work function comparable to that of metal K. However, its surface area is low (≈1 m2 g−1) because sintering occurs during high‐temperature annealing, which is needed to remove CaO layers formed by reaction with metal Ca that works as a reductant. We report a simple synthesis method for moderate‐surface‐area C12A7:e− (9–19 m2 g−1) by using a rapid thermal annealing (RTA) technique. The synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Furthermore, they reported that the effect of promoters follows the order of promoter IPs, with lower IPs resulting in greater effects as promoters (Cs > K> Na) . A similar mechanism was also confirmed for NH 3 synthesis over a Ru/electride catalyst (12CaO 7 Al 2 O 3 ) …”
Section: Resultssupporting
confidence: 70%
“…Furthermore, they reported that the effect of promoters follows the order of promoter IPs, with lower IPs resulting in greater effects as promoters (Cs > K> Na) . A similar mechanism was also confirmed for NH 3 synthesis over a Ru/electride catalyst (12CaO 7 Al 2 O 3 ) …”
Section: Resultssupporting
confidence: 70%
“…and 437 μmol g −1 h −1 for Re/MCM-41 [14] have been reported for conditions comparable to those applied in this study. In the case of Ru dispersed on electride, a rate of 3550 μmol g cat −1 h −1 has been reported at atmospheric pressure and 340°C [3]. Comparing the data in Table 1, a degree of influence of pretreatment gas can be seen.…”
Section: Resultsmentioning
confidence: 72%
“…This is the basis of the KBR Advanced Ammonia Process which is operated at lower pressure than in the Haber Bosch counterpart [2]. Investigations into Ru catalysed ammonia synthesis are on-going with very recent literature documenting very high activity for electride supported Ru catalysts [3]. Additional literature has reported that certain nitrides exhibit high activity, with Co 3 Mo 3 N based systems being particularly noteworthy [4][5][6], although high activity has also been documented for other systems such as Ni 2 Mo 3 N [4] which could offer advantages in terms of ease of nitridation [7].…”
Section: Introductionmentioning
confidence: 99%
“…So far, various transition metal catalysts such as Fe, Ru, Re and Co have been developed for this reaction. [3][4][5][6][7][8][9] Among them, Fe-based and Ru-based catalysts have been extensively used in ammonia plants all over the world. However, iron catalyst is kinetically sensitive to the changes in ammonia concentration, and the catalytic activity decreased greatly with increasing ammonia concentration of the reactant gas.…”
Section: Introductionmentioning
confidence: 99%